A healthy weight improves life satisfaction. (1st October 2018) - Habibov, Nazim; Auchynnikava, Alena; Luo, Rong; Fan, Lida
Summary: In this study, we examine the effects of having a healthy weight in form of a healthy body mass index (BMI) on life satisfaction using the data from a diverse sample of 27 post‐communist transitional countries. We find that a healthy BMI significantly raises life satisfaction, while an increase in BMI reduces life satisfaction. We also find that the positive effect of a healthy BMI on life satisfaction substantially diminishes as the political and economic situation improves. Equally, the positive effect of healthy BMI on life satisfaction is considerably lower for those who exhibit higher levels of institutional trust and express trust in government, parliament, and political parties. Classic regression models such as ordinary least squares (OLS) and ordered probit significantly underestimate the true effect of healthy BMI on life satisfaction. Such results suggest that unobserved confounders, measurement error, or their interplay appear to be the main source (s) of bias that eventually lead to a significant underestimation of the true effect of BMI on life satisfaction through classic regression models.